Factor Analysis Of The Implementation Of The Occupational Safety And Health Management System At The Lirboyo General Hospital, Kediri City - Lutfiana Ulfa; Novita Ana Anggraini; Wening Palupi Dewi (Journal of Hospital Management and Services, 2023)
The hospital is a workplace that has a risk of danger. Based on the Government Regulation of the Republic of Indonesia Number 50 of 2012 concerning the Implementation of the Occupational Safety and Health Management System (SMK3) states that SMK3 is part of the overall company management system in order to control risks related to work activities in order to create a safe, efficient and productive workplace. The Occupational Safety and Health Management System (SMK3) is part of the overall management system in order to control risks related to work activities in order to create a safe, efficient and productive workplace. The study aims to determine the factors implementing the Occupational Safety and Health Management System at the Liboyo General Hospital, Kediri City. The study aims to determine the factors implementing the Occupational Safety and Health Management System at the Liboyo General Hospital, Kediri City. The research method used is quantitative with a cross-sectional study design. The research data used primary data which was taken directly by filling out questionnaires for employees at Lirboyo General Hospital, Kediri City from August 2021 to October 2021. The sampling technique used simple random sampling with a population of 167 and a sample of 118. This study used Ordinal Regression analysis. . In this study, the results showed that there was an influence of the human resource quality factor variable on the implementation of SMK3 with a value of 0.003 and there was an influence of the law enforcement factor variable on the implementation of SMK3 with a value of 0.000. While the K3 monitoring factor variable has no influence on the implementation of SMK3 with a value of 0.486. Through the R Square table, it is known that the implementation factor of SMK3 at Lirboyo General Hospital, Kediri City, has an influence of 25.2%.